THE IMPACT OF PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE ON THE ADOPTION OF E- COMMERCE IN MALAYSIA - Johar; MGM; Jaharadak, Adam Amril bin; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The existing literature and trends suggest that e-commerce channels are fast becoming an integral part of the web based channel strategy. This paper takes a game theoretic approach to study, outlines and analyses the customer’s behaviour with respects to their perception and acceptance towards of adoption in electronic commerce. Furthermore, this research not only demonstrate on these contextual differences which influence consumer satisfaction with the purchase products or services using e-commerce, but also investigate the contextual constructs that make consumer satisfied or dissatisfied that lead to acceptance of e-commerce in Malaysia. Thus, this study explores the relationship between independent variables which are perceived usefulness, perceived ease of use, social culture influence and consumer advantages in explaining the dependent variable which is adoption of ecommerce in Malaysia.